2023
DOI: 10.3390/molecules28041855
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Alkane and Aldehyde Hydroxylation Reactions Mediated by In Situ Generated Iron(III)-Iodosylbenzene Adduct

Abstract: Previously synthesized and spectroscopically characterized mononuclear nonheme, low-spin iron(III)-iodosylbenzene complex bearing a bidentate pyridyl-benzimidazole ligands has been investigated in alkane and aldehyde oxidation reactions. The in situ generated Fe(III) iodosylbenzene intermediate is a reactive oxidant capable of activating the benzylic C-H bond of alkane. Its electrophilic character was confirmed by using substituted benzaldehydes and a modified ligand framework containing electron-donating (Me)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In the first case we have obtained direct kinetic and computational evidence for the formation of low-spin oxoiron(IV) via the dissociation process [ 40 ], whereas in the second case the peroxo-diiron(III) intermediate was the key intermediate [ 45 ]. As a continuation of these studies, five heterobidentate-ligand-containing model compounds, including the previously reported and fully characterized [Fe II (L 1−2 ) 3 ] 2+ [ 39 ], [Fe II (L 3 ) 3 ] 2+ [ 46 ] and [Fe II (L 4 ) 3 ] 2+ [ 47 ] (L 1 = 2-(2′-pyridyl)-1 H -benzimidazole, L 2 = 2-(2′-pyridyl)- N -methyl-benzimidazole, L 3 = 2-(4-thiazolyl)-1 H -benzimidazole and L 4 = 2-(4′-methyl-2′-pyridyl)-1 H -benzimidazole) and the novel [Fe II (L 5 ) 3 ] 2+ (L 5 = 2-(1 H -1,2,4-triazol-3-yl)pyridine), were selected to investigate the mechanism and the effect of the redox potential and the spin-state of the catalyst on the reactivity towards H 2 O 2 ( Scheme 2 ).…”
Section: Introductionmentioning
confidence: 93%
“…In the first case we have obtained direct kinetic and computational evidence for the formation of low-spin oxoiron(IV) via the dissociation process [ 40 ], whereas in the second case the peroxo-diiron(III) intermediate was the key intermediate [ 45 ]. As a continuation of these studies, five heterobidentate-ligand-containing model compounds, including the previously reported and fully characterized [Fe II (L 1−2 ) 3 ] 2+ [ 39 ], [Fe II (L 3 ) 3 ] 2+ [ 46 ] and [Fe II (L 4 ) 3 ] 2+ [ 47 ] (L 1 = 2-(2′-pyridyl)-1 H -benzimidazole, L 2 = 2-(2′-pyridyl)- N -methyl-benzimidazole, L 3 = 2-(4-thiazolyl)-1 H -benzimidazole and L 4 = 2-(4′-methyl-2′-pyridyl)-1 H -benzimidazole) and the novel [Fe II (L 5 ) 3 ] 2+ (L 5 = 2-(1 H -1,2,4-triazol-3-yl)pyridine), were selected to investigate the mechanism and the effect of the redox potential and the spin-state of the catalyst on the reactivity towards H 2 O 2 ( Scheme 2 ).…”
Section: Introductionmentioning
confidence: 93%
“…The structure and reactivity of the iodosylarene adduct of heme and non-heme Mn(III), Mn(IV) and Fe(III) complexes have been thoroughly investigated. Recent studies have shown that the metal-iodosylbenzene adduct itself can play an important role in transition metal-catalyzed oxidation reactions [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. For some multiple oxidation mechanisms, some of showed better reactivity than the corresponding metal-oxo intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Its reaction with H2O2 and PhIO results in the formation of µ-1,2-peroxo-diiron(III) and iron(III)-iodosylbenzene complexes, respectively [28][29][30]. The spectral properties, reactivity and kinetics of Fe III (OIPh) bearing PBI ligands towards cycloketones in nucleophilic Baeyer-Villiger reactions [15], and towards benzaldehydes and triphenylmethane in electrophilic C-H oxygenation reactions, were investigated in detail [27]. Significant progress has been made in the last three decades in the understanding and application of nonheme iron complexes in oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show that the nature of the equatorial ligands plays a decisive role in the redox potential values of iron-oxo complexes [18]. There are only a few examples in the literature where the role of precursor intermediates, such as Fe III OIPh, can be clearly demonstrated in C-H activation and oxygen atom transfer reactions [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Well-characterized penta-and hepta-coordinated Fe III OIPh intermediates were reported using tetradentate 13-TMC (13-TMC = 1,4,7,10tetramethyl-1,4,7,10-tetraazacyclotridecane) and hexadentate tpena (tpena = N,N,N'tris(2-pyridylmethyl)ethylenediamine-N′-acetate) ligands [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Based on experimental studies of (13-TMC)Fe III OIPh-mediated styrene epoxidation, a DOT mechanism was proposed, which is consistent with the theoretical calculation resulting in simultaneous cleavage of the I−O bond and O−C bond formation during the epoxide formation [ 18 , 36 ]. Related to this area, we investigated the reactivity of the in situ formed (PBI)Fe III OPh (PBI = 2-(2-pyridyl)benzimidazole) intermediate in oxygen atom transfer reactions towards thioanisole and styrene derivatives [ 45 , 46 , 47 ]. Based on mechanistic studies, we obtained clear evidence that the stoichiometric and catalytic thioanisole sulfoxidation reactions mediated by the Fe III OIPh intermediate proceeds via a DOT mechanism, in contrast to styrene oxygenation, where the epoxidation can be depicted by a nonconcerted ET mechanism [ 47 ].…”
Section: Introductionmentioning
confidence: 99%